APLIKASI STABILISASI RICE BRAN DALAM FOOD BAR BERBASIS TEPUNG SORGUM SEBAGAI PANGAN DARURAT - Lufi Karisma Rahmawati; Karseno Karseno; Nur Aini (JURNAL AGROTEKNOLOGI, 2020)
Indonesia is a country that is prone to natural disasters. In emergency situation, a special food design for disaster victims that is practical and nutritional is needed. Food bar is one example of practical food that is suitable for consumption in emergencies. The basic ingredients of food bars can be made from sorghum flour which is rich in nutritional value. So that its function as an emergency food is more optimal then a food bar is applied using a stabilized rice bran. The purpose of this research was to determine the process condition of rice bran stabilization to produce rice bran with good taste and aroma, the organoleptic character of food bars and the physical and chemical characteristics of the five best food bar products. The method used is an experimental method with RBD (Randomized Group Design). The factors studied consisted of two factors: the use of roasted temperatures (T) and food bar formulations (P). The results obtained were stable rice bran with the use of a temperature of 120oC and a stabilization time of 6 minutes, which will later be used in the process of making food bars. The best food bar product formulation was food bar with the ratio of sorghum flour and rice bran stabilizing flour as much as 85%: 15% (P4) which was baked at 130oC (T4). This formulation showed a total protein value of 14.99%, 30.08% fat, 40.27% carbohydrate and 246.01 kcal energy and has physical characteristics in the form of a hardness value of 1597.56 g force. Keywords: food bar, sorghum flour, stabilized rice bran